Pleural and peritoneal mesotheliomas in the Friuli Venezia Giulia register: data analysis from 1995 to 2015 in Northeastern Italy - D’Agostin, Flavia; De Michieli, Paola; Chermaz, Carolin; Negro, Corrado (Journal of Thoracic Disease, 2017)
Background: The Friuli Venezia Giulia Mesothelioma Register contains a case-list of 1,109 mesotheliomas (1,034 pleural, 75 peritoneal) during 1995–2015. Exposure data are available for almost all cases. The aim was to assess mesothelioma incidence in the Region, an area with several shipyards, and to investigate determinants of mesothelioma latency among occupational cases. Methods: Incidence rates were calculated. Univariate and multivariate analyses were performed to estimate latency time by anatomical site, gender, diagnostic period and industry sector. Results: Mesothelioma incidence rates among men were higher than among women during the overall period. The incidence of pleural mesothelioma in men leveled off until 2009 (6.50 per 100,000) with a slight decrease thereafter. For women, the rate increased until 2006 (1.31 per 100,000) and then remained relatively stable. The incidence of peritoneal mesothelioma in men was constant whereas rate among women increased during 2010–2015. The number of cases diagnosed during three-year periods remained level. In multivariate model, site and gender were not relevant for latency period whereas construction workers had a shorter latency than shipyard workers. Conclusions: Despite the asbestos ban since 1992, occupational exposure is still at risk. This highlights the need to assess exposure levels and to find a reliable health surveillance tool.